Efeitos do treinamento intervalado de alta intensidade de curto prazo sobre os biomarcadores de estresse oxidativo e danos musculares em ratos - Souza, Lúcio Marques Vieira (2018)
High intensity interval training (HIIT) has become very popular due to the dissemination of experimental results. HIIT promotes similar adaptations to longterm and low-intensity exercises, such as improvement in cardiorespiratory capacity, VO2max, respi- ratory metabolism, increased pulmonary ventilation, among others. However, these adaptations are obtained with much lower duration at maximum or submaximal intensities, with seconds or few minutes of interval. However, frequent performance may increase susceptibility to injury, promote chronic fatigue and overtraining, partly because of the high synthesis of reactive oxygen species (ROS). Stress is a state of imbalance between oxidation and oxidation reactions. However, the effects of HIIT on oxidative status and muscle damage are still not well understood in the scientific literature. The objective of this dissertation was to verify the effects of short-term HIIT on biomarkers of oxidative stress and muscle damage in Wistar rats. Thus, three studies were elaborated: 1) The effects of short-term HIIT on the markers of oxidative stress and muscle damage were evaluated; 2) It was sought to characterize the responses of cardiac oxidative stress markers to HIIT in rats. 3) The effects of twelve consecutive sessions and on different days of HIIT on the markers of hepatic oxidative stress were verified. In studies 1 and 2 significant changes were found in only one marker of oxidative damage, a fact that did not happen in study 3. Still on study 1 there were no changes in the markers of muscle damage, however there was a significant reduction in a marker of defense antioxidant. In studies 2 and 3 there were no significant changes in antioxidant capacity. It is concluded that HIIT is performed on consecutive or distinct days, and depending on tissue it may or may not promote liver, heart and muscle damage in rats.